Naturally occurring infection of Pekin duck embryos by duck hepatitis B virus. - O'Connell, A P (1983)
We tested the hypothesis that duck hepatitis B virus (DHBV) is a naturally occurring congenital infection of Pekin duck embryos. Of 219 embryos, 5-25 days after being laid, sera from 30 were found to be positive for endogenous DNA polymerase activity characteristic of hepatitis B-related viruses. The presence of the duck virus was confirmed by hybridization with cloned DHBV DNA. Viral DNA was also found in the livers of embryos incubated for 12 or 18 days. Electrophoretically different forms of DHBV DNA were identified in liver extracts that were not present in serum. These additional liver forms probably represent viral replication intermediates. These observations suggest that the vertical route is a major pathway of DHBV transmission and that viral replication may be initiated by the 12th day of embryonic life.